The CXCL1-CXCR2 Axis Mediates Tubular Injury in Diabetic Nephropathy Through the Regulation of the Inflammatory Response - Tang, Hanfen; Yang, Ming; Liu, Yinghong; Liu, Hong; Sun, Lin; Song, Panai (Frontiers in Physiology, 2021)
Diabetic nephropathy (DN) is one of the most severe complications of diabetes. Inflammation mediated by inflammatory factors is thought to accelerate the progression of renal damage in DN. However, which inflammatory factors mediate the inflammatory response in DN remains unclear. In this study, we determined that the CXCL1-mediated inflammatory response may play an essential role in DN progression through bioassays. Subsequently, we observed that the expression of CXCL1 and its receptor (CXCR2) was significantly increased in the kidneys of mice with HFD+STZ induced diabetes and DN patients. In addition, inhibition of the CXCL1/CXCR2 axis by repertaxin alleviates renal inflammation and pathological damage in the kidneys of db/db mice. Finally, we noted that the CXCL1/CXCR2 axis might lead to inflammatory damage through phosphorylated NF-κB and further activate the NLRP3 inflammasome. Our results revealed the role of the CXCL1/CXCR2 axis in DN progression for the first time, which may be a novel therapeutic target for DN.